Analisis Keterampilan Metakognitif Siswa Dalam Menyelesaikan Soal Geometri Dimensi Dua - Atmojo, Danar, Masduki, S.Si, M.Si (2016)
This study aimed to describe the profile of metacognitive skills of students with high math ability, medium, and low in solving the two-dimensional geometry from the aspects of metacognitive skills of planning, monitoring and evaluasi. Type this research is qualitative descriptive. The timing of the studies in the second semester of the 2015/2016 academic year. Subjects in this study were class X TKJ SMK Muhammadiyah 5 Karanganyar totaling 21 students. The data collection technique using the test method, interviews, observation and documentation. Data analysis techniques carried out in three stages: data reduction, exposure data, and conclusions or verification.The results showed that students who have high math skills meet the indicator metacognitive skills in planning, monitoring and evaluation. Students who have math skills are fulfilling indicator metacognitive skills in the planning stages, but does not fully comply indicators metacognitive skills in monitoring and evaluation stages, while students with low math skills do not meet the indicator metacognitive skills in planning, monitoring and evaluasidalam solve the problem.